Vegetation unit assignments: phytosociology experts and classification programs show similar performance but low convergence. Issue 4 (7th August 2020) - Maciejewski, Lise; Pinto, Paulina E.; Wurpillot, Stéphanie; Drapier, Jacques; Cadet, Serge; Muller, Serge; Agou, Pierre; Renaux, Benoît; Gégout, Jean‐Claude
Abstract: Aims: Assigning vegetation plots to vegetation units is a key step in biodiversity management projects. Nevertheless, the process of plot assignment to types is usually non‐standardized, and assignment consistency remains poorly explored. To date, the efficiency of automatic classification programs has been assessed by comparing them with a unique expert judgment. Therefore, we investigated the consistency of five phytosociology expert judgments, and the consistency of these judgements with those of automatic classification programs. Location: Mainland France. Methods: We used 273 vegetation plots distributed across France and covering the diversity of the temperate and mountainous forest ecosystems of Western Europe. We asked a representative panel of five French organizations with recognized expertise in phytosociology to assign each plot to vegetation units. We provided a phytosociological classification including 228 associations, 43 alliances and eight classes. The assignments were compared among experts using an agreement ratio. We then compared the assignments suggested by three automatic classification programs with the expert judgments. Results: We observed small differences among the agreement ratios of the expert organizations; a given expert organization agreed with another one on association assignment one time in four on average, and one time in two on alliance assignment. The agreement ratios of the automatic classification programs were globally lower, but close to expert judgments. Conclusions: The results support the current trend toward unifying the existing classifications and specifying the assignment rules by creating guiding tools, which will decrease inter‐observer variation. As compared to a pool of phytosociology experts, programs perform similarly to individual experts in vegetation unit assignment, especially at the alliance level. Although programs still need to be improved, these results pave the way for the creation of habitat time series crucial for the monitoring and conservation of biodiversity. Abstract : We assessed for the first time the consistency of vegetation unit assignments by five experts and three automatic classification programs. We observed a lack of consistency among experts, and programs performed quite similarly as experts did. The results support the current trend toward unifying the existing classifications, and pave the way for the creation of habitat time series crucial for monitoring.